Gagasan Penyederhanaan Jumlah Partai Politik Dihubungkan Dengan Sistem Pemerintahan Republik Indonesia - Mexsasai Indra (Jurnal Ilmu Hukum, 2010)
Political reforms in 1998 which was followed by afree and democratic elections in 1999, has a fairly fun-damental change relationship patterns that charac-terized the President and the Parliament many politi-cal parties that play a role in the constitutional struc-ture. Because it came back the idea of simplificationis a political party. efforts to simplify the number ofpolitical parties is a must in order to support an effec-tive presidential system of government, while the ef-fort to do that is by simplifying the number of politicalparties naturally through the electoral threshold,tighten the terms of the establishment of political par-ties dismaping it is also the reality that there is cur-rently a clear need for regulation of the coalition sys-tem.